Diligence and trustworthiness : the qualities of muslim employee - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
This chapter discusses the qualities of work ethics desired from a Muslim employee, whether local or migrant namely, diligence and trustworthiness. In relation to the above, reference is made to the Qur’an, in Surah al Qasas (28): verses 21 to 27. The verses contain the story of Prophet Musa (a.s.) who had, inter alia, assisted two women in watering their flocks and thereafter, was employed by the family despite being a stranger because it was realised that he possessed the true qualities of a sincere worker.